Diagnostic Performance of Vibration Controlled Transient Elastography in Liver Transplant Recipients - Siddiqui, Mohammad Shadab (Clin Gastroenterol Hepatol, 2020)
BACKGROUND & AIMS: Vibration-controlled transient elastography (VCTE) is a non-invasive tool for detecting hepatic steatosis and fibrosis in patients who have not received liver transplants. We aimed to evaluate the diagnostic performance of VCTE in detection of hepatic steatosis and fibrosis in patients who have undergone liver transplantation. METHODS: We performed a prospective study of 99 liver transplant recipients assessed by VCTE using a standard protocol. Controlled attenuation parameter cutoff values for pairwise steatosis grade and liver stiffness measurements (LSM) and cutoff values for pairwise fibrosis stage were determined using cross-validated area under the receiver operating characteristics (AUROC) curve analyses. We calculated sensitivity (fixed at 90%) and specificity (fixed at 90%) values. RESULTS: A controlled attenuation parameter cutoff value of 270 dB/m detected any hepatic steatosis with an AUROC of 0.88 (95% CI, 0.78–0.93). VCTE detected steatosis grades 2–3 vs 0–1 with an AUROC of 0.94 (95% CI, 0.89–0.99) and steatosis grade 3 vs 0–2 was similar and AUROC of 0.89 (95% CI, 0.83–0.96). When we used an LSM cutoff value of 10.5 kPa, VCTE identified patients with advanced fibrosis (fibrosis stages≥3) with an AUROC of 0.94 (95% CI, 0.88–0.99). At fixed sensitivity, the cutoff LSM value of 10.5k Pa excluded advanced fibrosis with a negative predictive value of 0.99. At fixed specificity, the cutoff LSM value of 16.9 kPa detected advanced fibrosis with a sensitivity of 0.86, a positive predictive value (PPV) of 0.40, and a negative predictive value of 0.99. CONCLUSIONS: VCTE accurately detects hepatic steatosis and fibrosis in recipients of liver transplants. This non-invasive method might be used to identify patients in need of confirmatory liver biopsy analysis.